Potentiation of Inhibition of Wild-Type and Mutant Human Immunodeficiency Virus Type 1 Reverse Transcriptases by Combinations of Nonnucleoside Inhibitors and d- and l-(β)-Dideoxynucleoside Triphosphate Analogs - Maga, Giovanni (American Society for Microbiology, 2001)
Combinations of reverse transcriptase (RT) inhibitors are currently used in anti-human immunodeficiency virus therapy in order to prevent or delay the emergence of resistant virus and to improve the efficacy against viral enzymes carrying resistance mutations. Drug-drug interactions can result in either positive (additive or synergistic inhibition) or adverse (antagonistic interaction, synergistic toxicity) effects. Elucidation of the nature of drug interaction would help to rationalize the choice of antiretroviral agents to be used in combination. In this study, different combinations of nucleoside and nonnucleoside inhibitors, including d- and l-(β)-deoxy- and -dideoxynucleoside triphosphate analogues, have been tested in in vitro RT assays against either recombinant wild-type RT or RT bearing clinically relevant nonnucleoside inhibitor resistance mutations (L100I, K103N, Y181I), and the nature of the interaction (either synergistic or antagonistic) of these associations was evaluated. The results showed that (i) synergy of a combination was not always equally influenced by the individual agents utilized, (ii) a synergistic combination could improve the sensitivity profile of a drug-resistant mutant enzyme to the single agents utilized, (iii) l-(β)-enantiomers of nucleoside RT inhibitors were synergistic when combined with nonnucleoside RT inhibitors, and (iv) inter- and intracombination comparisons of the relative potencies of each drug could be used to highlight the different contributions of each drug to the observed synergy.